EVALUATION IN TEACHING JOKYUU DOKKAI (Case Study of 6th Semester Students, Japanese Literature Department, Faculty of Letters, Udayana University) - Anggraeny, Renny (Chi'e: Journal of Japanese Learning and Teaching, 2019)
Reading is one of the four language skills, with the ability of reading, hopefully the language learners especially the Japanese language learners, the 6th semester student of Japanese Literature Department, Faculty of Letters, Udayana University can understand the text well what is implied as well which is expressed in the text then the purpose is reached. There is the test is held to require whether the student can understand the text. The reading evaluation is really important to measurement the level of the Japanese learner ability in understanding the materials that has been given in the classroom then the main goal can be achieved well. The level of reading ability consists of the level of memorizing, level of understanding, level of application, level of analysis, level of synthesis and level of evaluation.The problems examined evaluation in teaching Jokyuu Dokkai with using the form test of reading ability in 6th semester Jokyuu Dokkai courses, how using the reading ability level in 6th semester Jokyuu Dokkai courses and how using the Penilaian Acuan Patokan (PAP) or the benchmark reference assessment applied in 6th semester Jokyuu Dokkai courses and and how reading ability test results in 6th semester Jokyuu Dokkai courses.The method used in this research is the descriptive qualitative method. The data sources used in this study are all the students of A class and B class of 6th semester in Jokyuu Dokkai courses, Japanese Literature Department, Faculty of Letters, Udayana University. The data used in this study is the reading question and student questionnaire results. The result of the analysis is using the triangulation technique. Triangulation Patton (in Lexy J. Moleong, 2012: 330), there are two strategies for measuring the validity of data, the first is by checking the degree of confidence in the data obtained from the data technique and the second is by checking the information from the data in the same way